Професійні компетентності та особистісні якості керівника служби безпеки в організації: діагностика та формування - Адоніна, В. В. (Ways to Improve Construction Efficiency, 2013)
There is a necessity to set forth certain requirements to personality of candidate on position that it follows to take into account at a reception on work, but also to work out criteria and programs of psychological accompaniment of all official activity of employees.